Evaluation of Baseline Cortisol, Endogenous ACTH, and Cortisol/ACTH Ratio to Monitor Trilostane Treatment in Dogs with Pituitary‐Dependent Hypercortisolism. (23rd May 2013) - Burkhardt, W.A.; Boretti, F.S.; Reusch, C.E.; Sieber‐Ruckstuhl, N.S.
<x xml:space="preserve">Abstract</x> Background The effectiveness of trilostane treatment is currently monitored by regular ACTH stimulation tests, which are time‐consuming and expensive. Therefore, a monitoring system without a stimulation protocol and with less client expense would be preferable. Hypothesis/Objectives The aim of our study was to evaluate if baseline cortisol, endogenous ACTH (ACTH) concentration or the baseline cortisol to ACTH ratio (cortisol/ACTH ratio) could replace the ACTH stimulation test. Animals Forty trilostane‐treated dogs with pituitary‐dependent hypercortisolism (PDH) were included in this prospective study. Methods A total of 148 ACTH stimulation tests and 77 ACTH concentrations and cortisol/ACTH ratios were analyzed. Control of cortisol release was classified according to cortisol concentration after ACTH administration as excessive (<1.5 μg/dL; group 1), adequate (1.5–5.4 μg/dL; group 2), or inadequate (>5.4 μg/dL; group 3). Results Baseline cortisol concentrations had considerable overlap between excessively, adequately, and inadequately controlled dogs. Only baseline cortisol >4.4 μg/dL (in 12% of tests) was a reliable diagnosis of inadequate control. Endogenous ACTH concentrations did not differ between groups. The overlap of the cortisol/ACTH ratio between groups was large. Correct classification was only possible if the cortisol/ACTH ratio was >15, which occurred in 4% of tests. Conclusions and Clinical Importance To monitor trilostane treatment the ACTH stimulation test cannot be replaced by baseline cortisol, ACTH concentration, or the cortisol/ACTH ratio.